PENGARUH SERVICE QUALITY, CUSTOMER EXPERIENCE DAN PERCEIVED VALUE TERHADAP LOYALITAS PELANGGAN MASKAPAI AIRASIA DI PEKANBARU - Syofiatul Safitri; Nadya Nurwahyuni (Lembaga Pengembangan Kinerja Dosen, 2025)
Business competition in Indonesia is increasing, many companies operating in the same field, offering similar services make competition unavoidable, one of which is in the aviation industry. This study aims to determine the effect of service quality, customer experience and perceived value on customer loyalty of airlines using the services of the AirAsia Pekanbaru Representative Office. This study uses a quantitative method. The sampling technique is Purposive Sampling with a sample size of 98 respondents. The data obtained were processed using SPSS software version 25. The results of this study are: (1) service quality has a significant effect on customer loyalty, (2) customer experience has a significant effect on customer loyalty, (3) perceived value has a significant effect on customer loyalty, (4) service quality, customer experience and perceived value together can increase customer loyalty.